The salmonid cathelicidins: a gene family with highly varied C-terminal antimicrobial domains. - SCOCCHI, MARCO; SALGARO R; BOCIEK K; PALLAVICINI, Alberto; GENNARO, RENATO (2009)
The cathelicidin family of host defence peptides is regarded as an important component of the host innate immune system. Its members have been found in mammals, birds, primitive vertebrate Atlantic hagfish and, most recently, also in ray-finned fish such as rainbow trout and Atlantic salmon. By using genomic PCR amplifications and RT-PCR tissue analyses we have here investigated and characterized the cathelicidin genefamily in three salmonids: brown trout (Salmo trutta fario), brook trout (Salvelinus fontinalis) and grayling (Thymallus thymallus). One or two different genes were found in each species coding for almost identical cathelin-like domains and largely varied cationic C-terminal regions. Multiple alignment of the amino acid sequences let us recognize two distinctive hallmarks of these peptides: the presence of a high number of serine and glycine residues, which may collocate them in a new class of antimicrobial peptides, and of the six-amino-acid repeated sequence RPGGGS detected in a variable number of copies among different cathelicidins. The high variation in length and sequence of this region suggests the existence of a genetically unstable region similar to that found in some mammalian cathelicidins.